Why Do People Give Less Weight to Advice the Further It Is from Their Initial Opinion? - Francesco Ravazzolo; Øistein Røisland (Norges Bank, 2010)
Experimental studies on decision making based on advice received from others find that the weight put on the advice is negatively related to the distance between the advice and the decisionmaker's initial opinion. In this paper, we show that the distance effect can follow from rational signal extraction when the decisionmaker has imperfect knowledge about the advisor's competence. What drives the result is the assumption that the decisionmaker is better informed about her own competence than about the advisor's competence.
hdl:11250/2497460
Keywords: C11; D78; D82; D83; 330; distance effect; policy decision making; signal extraction; uncertainty